Pengasuhan Ideal Bagi Generasi Alpha - Wa Ode Yahyu Herliany Yusuf; Widia Wati Bustaming; Farnisa Rahmatia; Zanurhaini Zanurhaini; Salsabillah. H; Anissa Nur Salawati; Yeni Yeni; Rini Rini; Maliati Maliati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The alpha generation is the generation born in 2011 and is expected to end in 2025. This generation is also called the digital generation. This alpha generation was raised in the technological era and also has a very important influence on the progress of the times. His upbringing must also receive special attention, especially from those closest to him, namely parents. Ideal parenting for the alpha generation needs to be implemented by parents. The type of research we use is qualitative research. Where data is collected by means of interviews, documentation and observation. And then conclusions are drawn regarding ideal parenting for the alpha generation. The results of this research show that there is a very close relationship with ideal parenting and the alpha generation. This is shown by the results of interviews that we have conducted that many parents complain about their children's attitudes, and parents lack understanding about parenting.